Music and the paediatrician - Senanayake, M.P. (My University, 2012)
Place of music in the practice of paediatrics has received scant attention although physicians and neurologists, in particular, are showing an increasing interest in this topic1. This article attempts to highlight the link between music and child development, music as a feature in specific paediatric conditions and the place of music therapy in newborn nurseries.